Tourism During Pandemic of Covid-19: Analysis of The Situation and Ways Out of The Crisis - Iryna KYRYLIUK; Valentyna SHAPOVAL; Inna POVOROZNIUK; Tetyana HERASYMENKO; Oksana LYTVYN (Communications of International Proceedings, 2020)
The article analyses the situation on the market of the tourism industry in the context of the COVID-19 pandemic. The global crisis caused by the COVID-19 pandemic has radically changed the activities of the tourism industry around the world. Restrictions that have been implemented almost all over the world, especially the closure of interstate borders, caused significant damage to the tourism industry. The tendencies of losses of the tourist branch are determined and the attention is focused on the problems of significant decrease of tourist activity and level of employment in the tourism and related fields. The approaches of the governments of some tourist-attractive countries of the world are systematized for minimizing the consequences of the COVID-19 pandemic and stimulating the recovery of the tourism sector. Practical proposals for overcoming the crisis are presented, its implementation will reduce the level of negative impact of the pandemic on the economy of the tourism industry. It is substantiated that there is a need of search of innovative models, introduction of new approaches, application of information technologies, improvement of the general model of communications in the conditions of tourists restriction on movement; all of that will promote access to tourist objects and will attract new audience, develop new skills and support transition to new conditions. Smart tourism is a catalyst for change that has significant potential, and it is a source of information for customers about the territory, in addition this is a quality communication channel with tourism service providers. Gamification is part of the modern information and communication infrastructure and is gaining popularity in the marketing activities of companies, using the best ideas borrowed from loyalty programs, game mechanics and behavioural economics and creating mechanisms for the participation of tourists in business processes.
Keywords: Tourism; Pandemic; Global Tourism Industry; Marketing Innovations.